Kode Etik Profesi Guru di Era Globalisasi: Menghadapi Tantangan dan Peluang - Radianti, Radianti; Ramadhan, Ilham; Amal, Amin Ikhlasul; Nasution, Abdul Fattah (Pusdikra Publishing, 2024)
Amidst the rapidly advancing tide of globalization, the role of teachers is becoming increasingly crucial in shaping a future generation capable of competing globally. However, the challenges faced by teachers are not light. The era of globalization brings significant changes to the educational paradigm, in terms of technology, values, and culture. Therefore, it is important for us to understand the professional code of ethics for teachers in this era of globalization, considering their vital role in shaping the character and abilities of future generations. Several previous studies have highlighted the challenges and strategies of teachers in facing the professional code of ethics in the era of globalization, as well as understanding teachers' perceptions of professional ethics in the context of globalization. The aim of this discussion is to provide a deeper understanding of the moral and ethical foundation that teachers must possess in carrying out their duties. In this paper, a descriptive qualitative approach is utilized to delve into the understanding of the professional code of ethics for teachers in the era of globalization. Through this understanding, it is hoped that teachers can fulfill their roles with integrity, professionalism, and high responsibility, thereby creating a safe, inclusive, and competitive learning environment in this era of globalization.